Templated Crisis Communication for People With Disabilities, Access and Functional Needs (Journal of International Crisis and Risk Communication Research, 2022)
Despite the Americans with Disabilities Act being more than 30 years old, many government institutions fail to fully support their constituents, and provide understandable and actionable crisis communications before, during, and after emergencies and disasters. When residents do not effectively receive, understand, and act on crisis communications in a timely manner, life safety issues can occur. People may choose not to evacuate when necessary or lack the information for properly sheltering-in-place. These and other bad decisions can be deadly. Crisis communications, as a subset of risk communications, should be aligned with all the disaster phase cycles—the before, during, and after stages of disasters and crises—so that impacted residents obtain complete information they can use. U.S. government websites, including posted crisis communications public releases, must be compliant with the Americans with Disabilities Act (ADA) under Title II and they should use templated crisis communications available in other languages, English-only audio recordings, and videos of American Sign Language.